Introduction to information technology a reference manual - Lansigan, Rolando ([Place of publication not identifed] : [publisher not identified], 2004)
This manual is equipped with comprehensive information, with diagrams and screen outputs needed by the students for them to fully understand and have a concrete view of the computer world.
Chapter I. Data Processing -- Chapter II. Computer Concept -- Chapter III. Hardware -- Chapter IV. Software -- Chapter V. Peopleware and Dataware -- Chapter VI. Number System -- Chapter VII. Windows 95 -- Chapter VIII. Multimedia -- Chapter IX. Internet -- Chapter X. Ms-Word -- Chapter XI. Introduction to Microsoft Excel -- Chapter XII. Excel Basics -- Chapter XIII. Getting Started in Excel -- Chapter XIV. Working with Workbooks and Worksheets -- Chapter XV. Entering Data and Selecting Cells -- Chapter XVI. Editing and Formatting Worksheets -- Chapter XVII. Printing Worksheets -- Chapter XVIII. Creating Formulas -- Chapter XIX. Working with Charts .
Keywords: INFORMATION TECHNOLOGY